Las políticas y control interno del grupo Educativo Britannia-Cambridge School de la ciudad de Cuenca y sus efectos en la toma de decisiones, período 2015. - Cordones Naranjo, María Fernanda (2017)
The constant competition in existing markets makes to all kinds of organizations to implement strategies to eliminate the waste of resources and to be more competitive within the market. The policies formulated by the managers for the internal control of the organizations are the fundamental part for the control and decision making. The non-application of policies means that resources are not controlled by the managers of an organization. There are expenses that are not specific to the line of business and cannot be controlled, this leads to incorrect decision making and minimal or non-existent control of this type of expenses. For the proper control in organizations strategies must be implementation, internal control measures and the implementation of both administrative and financial policies. The present research was carried out in the Britannia Educational Group - Cambridge School of the city of Cuenca during the year 2015, in the same participation the personnel in charge of the administration of the resources as well as those responsible in the decision making mainly to the directors of the institution. It proposes the concrete application of both administrative and financial policies that will help the normal development and the optimization of resources in the educational group. The manual of functions by competences was made for all the personnel, as well as the Internal Financial control policies within the possibilities of the policies of petty cash, banks, teachers – students receivable accounts, inventories, payable accounts extras -teachers, income, pay rolls among others.